PENGARUH FAKTOR SOSIAL, FAKTOR PRIBADI DAN RELIGIUS TERHADAP KEPUTUSAN ORANG TUA MEMILIH SD EL MA’ARIF- PASAMAN BARAT - Erdawati Erdawati (Jurnal Apresiasi Ekonomi, 2017)
Education of Elementary School especiallyin West Pasaman had sufficient number of primary school, and almost certainly on every Jorong there were primary schools, they competed to get students by improving the quality of education, facility and other infrastructure facilities. Departing from this rivalry private schools began to manifest themselves with reference to quality, including service program of boarding school for school-based Religion. EL-ma'arif elementary school appeared the excellence both on the quality of education quality from learning activities and the activities of self-development. Most private primary schools made themselves as a choice by parents for their children’s education. Social factors, personal factors and religious factors are among the factors that can be affected parents in making decision. The data collection in this study conducted by using questionnaire that included an instrument as measurement of population variable were parents of students that active in academic year 2006/2017 about 326, the sampling used Slovin formula obtained sample of 77 people. The result of multiple linear regression analysis of social factors, personal factors and religious factors contributed 33.3% toward the decision of parents choose El-Maarif elementary school. The practical implications of this research toward the management were to be able to find the strategies or factors for the development of a better education. Keywords : Social factor, personal factor, religion factor, parents’ decision